Experimental Investigation of Water-Rich Fully Weathered Granite on Water Bursting and Mud Bursting - Zheng, Suping (Frontiers in Earth Science, 2021)
In order to investigate the mechanism of water-rich and fully-weathered granite on the water bursting and mud bursting, the single-factor variable method is adopted in this research. The factors, such as particle size gradation, initial porosity, water pressure, confining pressure and anti-outburst thickness are chosen in this paper, to evaluate each factor on the evolutions of sand gushing, porosity, permeability, fine particle concentration and water gushing velocity. The results indicate that particle loss is the most critical reason for inducing the water bursting and mud bursting of the water-rich and fully-weathered granite. The transition of the water bursting symptoms from linear to non-linear is the most significant feature. Soil particles with a larger Talbol power index is more likely to lead to water bursting. In addition, there is a critical water pressure that controls the occurrence of the water bursting and mud bursting. It is found that when the confining pressure reaching the soil yield strength, the evolution of water bursting and mud bursting is obviously independent of the increase of confining pressure. The increase of the anti-outburst thickness also can effectively limit the risk of water bursting and mud bursting.